Effective non-relativistic potential for higher-derivative gravity in D dimensions - Accioly, A.; Mukai, H.; Azeredo, A. (Iop Publishing Ltd, 2001)
An expression for computing the effective non-relativistic potential for higher-derivative gravity in D dimensions is obtained.